A solar-driven plant to produce power, cooling, freshwater, and hot water for an industrial complex. (November 2021) - Sadeghzadeh, Milad; Ghorbani, Bahram; Ahmadi, Mohammad Hossein; Sharma, Shubham
Abstract: In this investigation, a solar-driven multi-generation plant is developed and studied through exergy assessment. The developed integrated system is designed to provide power, cooling, freshwater, and hot water for an industrial complex. The designed layout consists of solar parabolic trough collectors as the main driver which can provide the driving temperature of 220 °C at its maximum output, a combination of Kalina cycle and ejector refrigeration to produce cooling load and power for the industrial complex, and multi-effect distillation unit to generate freshwater. Exergy assessment shows that collectors are the most destructive equipment in the designed layout. The exergy efficiency of the solar parabolic trough collectors reaches to 49.36%. The total exergy efficiency of the presented system achieves up to 25.92%. The designed system provides 32.27 kW of power, 156.3 kW of cooling, 4.907 m 3 /h of freshwater, and 1.449 m 3 /h of hot water at 61.4 °C. Additional assessments show that vapor generator pressure is a key factor on the output performance of the presented system. It has been shown that the total exergy efficiency of the system decreases by increasing the vapor generator pressure. The economic assessment illustrates that the investment return period and the prime cost of the product are 3.958 years and 1.773 US$/m 3 freshwater, respectively.